PENINGKATAN KOMPETENSI SOSIAL GURU MELALUI COACHING DI SDN KALONGAN 01 UNGARAN TIMUR - Chory Praseptiana; Ngatijah; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the application of coaching techniques in increasing the social competence of teachers at SDN Kalongan 01 Ungaran Timur. The research method used is qualitative with a case study approach. Data was collected through interviews with teachers and students, observations. The results of the research showed that there was an increase in the social competence of teachers at SDN Kalongan 01 after coaching was carried out. It can be seen from the achievements of the Education report card at SDN Kalongan 01, indicator E.1.2. Participation of the Education Unit residents has increased after coaching was carried out by the school principal.